Associations of visceral adipose tissue adipokines with metabolic disorders in abdominal obesity - O. V. Tuzovskaia; Ya. V. Polonskaya; E. V. Garbuzova; E. V. Kashtanova; Yu. I. Ragino (Бюллетень сибирской медицины)
Aim. To identify associations of visceral adipose tissue adipokines with metabolic disorders in abdominal obesity.Materials and methods. The study included 101 individuals aged 25–65 years (51 men). For all patients, questionnaires were completed, anthropometric measurements and 3 measurements of blood pressure were performed, fasting blood was sampled, and biopsies of visceral adipose tissue were collected during elective surgery. The parameters of the lipid profile and glucose levels were determined in the blood by enzymatic methods. Homogenates from biopsies of visceral adipose tissue were prepared. The blood levels of adiponectin, adipsin, lipocalin-2, plasminogen activator inhibitor type 1 (PAI-1), and resistin were measured, and homogenates of adipose tissue were obtained by the multiplex analysis. Sex hormone levels in the blood of all patients (estradiol in women, testosterone in men) were determined by the enzyme-linked immunosorbent assay (ELISA) kits.Results. We identified correlations between serum levels of adipsin and adipose tissue and between adipsin from adipose tissue and PAI-1 in the blood serum. A weak negative relationship was found between the level of adiponectin and waist circumference, body mass index, and insulin resistance indices: triglyceride glucose index (TyG), lipid accumulation product (LAP), and visceral adiposity index (VAI). The level of adiponectin in visceral adipose tissue was inversely correlated with overweight in males and in the 45–65 age group. The level of resistin in visceral adipose tissue showed an inverse correlation with diastolic blood pressure, which persisted in the age group of 25–44 years.Conclusion. Of the studied adipokines, a relationship with cardiometabolic parameters was shown for adiponectin and resistin. At the same time, adiponectin was inversely correlated with overweight in the group of men and in the age group of 45–65 years, while resistin was inversely correlated with diastolic blood pressure in the age group of 25–44 years.